Effect of Sodium Fluoride-Hydrofluoric Acid Systems on Dentin of Human Molars - Rim, Ki Ho; Kim, Ui Hun; Hong, Un Sung; Son, Man Bok; Sin, Ye Song; Hyon, Sun Jong; Kim, Jin Hyok (Medical Science Journal for Advance Research, 2026)
Fluoride is known to react with dental dentin to produce calcium fluoride or fluorapatite to close dentin tubules to treat hypersensitivity. However, the formation of calcium fluoride or apatite is common in the recurrent disease, with rapid disappearance by mechanical or acidic stimuli. We have focused our attention on the fact that the newly developed NaF-HF gel has high chemical reactivity and a rapid rate of calcium fluoride formation in response to dental inorganic substrates and have chosen the research project to investigate the effect of this fluoride on human dental dentin. The main reaction product on fluoride-applied human molar dentin surfaces is fluoride apatite, whose production is enhanced by the number of fluoride applications and gelatinization is higher than that of the solution. When fluoride is applied and acid and mechanical stimulation is applied 28 days after immersion in artificial saliva, the acid stimulation has a greater effect on human molar dentin tubule closure than mechanical stimulation.